Optimisation of yogurt mousse dairy protein levels: a rheological, sensory, and microstructural study - Casanova-Yepes, H. (2022)
The present work aimed to optimise the skimmed milk powder (SMP) and whey protein concentrate (WPC) levels in order to obtain the best yogurt mousse in terms of rheological, sensory, and microstructural properties by using the response surface methodology. The methods consisted of rheological tests (large and small deformations), sensory profiles, particle size distributions, and differential interference contrast microscopy. The factors were SMP (5.3 - 10.7%) and WPC (2 - 4%), and the responses of the central composite design were the rheological parameters. A non-fermented mousse was employed as a standard. The results indicated that both SMP and WPC had positive and significant influence over the storage, loss, elastic moduli, and over the creep viscosity of yogurt mousses. A formulation containing 10.7% SMP and 2% WPC presented similar rheological and sensory characteristics to the standard mousse. There were microstructural differences between the optimal and standard samples, thus suggesting that the fermentation process influences the microstructure and texture of the product. We suggest more studies related to the variation of other nutrients (i.e.,fat and sugar) of this product in order to fully understand its rheological, sensory, and microstructural behaviour.